Neurological Manifestations of SARS-CoV-2 Infection: Protocol for a Sub-analysis of the COVID-19 Critical Care Consortium Observational Study - Battaglini, Denise; Premraj, Lavienraj; Griffee, Matthew; Huth, Samuel; Fanning, Jonathon; Whitman, Glenn; Bastos Porto, Diego; Arora, Rakesh; Durham, Lucian; Gnall, Eric; Amato, Marcelo; Williams, Virginie; et al. (Frontiers in Medicine, 2022)
Introduction: Neurological manifestations and complications in coronavirus disease-2019 (COVID-19) patients are frequent. Prior studies suggested a possible association between neurological complications and fatal outcome, as well as the existence of potential modifiable risk factors associated to their occurrence. Therefore, more information is needed regarding the incidence and type of neurological complications, risk factors, and associated outcomes in COVID-19. Methods: This is a pre-planned secondary analysis of the international multicenter observational study of the COVID-19 Critical Care Consortium (which collected data both retrospectively and prospectively from the beginning of COVID-19 pandemic) with the aim to describe neurological complications in critically ill COVID-19 patients and to assess the associated risk factors, and outcomes. Adult patients with confirmed COVID-19, admitted to Intensive Care Unit (ICU) will be considered for this analysis. Data collected in the COVID-19 Critical Care Consortium study includes patients’ pre-admission characteristics, comorbidities, severity status, and type and severity of neurological complications. In-hospital mortality and neurological outcome were collected at discharge from ICU, and at 28-days. Ethics and dissemination: The COVID-19 Critical Care Consortium main study and its amendments have been approved by the Regional Ethics Committee of participating sites. No further approval is required for this secondary analysis. Trial registration number: ACTRN12620000421932